KNOWLEDGE OF HEALTH IMPLICATIONS OF SEXUALLY TRANSMITTED INFECTIONS (STIS) POSSESSED BY UNDERGRADUATES OF UNIVERSITY OF NIGERIA, NSUKKA - Odo, A.N; Ojiaku, E.U; Okpala, F.I. (International Journal of Human Kinetics, Health and Education, 2023)
The purpose of the study was to determine the level of knowledge of health Implications of Sexually Transmitted Infections (STIs) possessed by undergraduates of University of Nigeria, Nsukka (UNN). Three research questions were formulated to guide the study. The descriptive research design was used for the study. The population for the study comprised of all the undergraduates of the university for 2012/2013 academic session. The sample size for the study consisted of 200 respondents, selected using multi-staged sampling procedure. The instrument for data collection was the researchers’ structured questionnaire, which was validated by three research experts from the Department of Health and Physical Education, University of Nigeria, Nsukka. The reliability of the instrument was also established and reliability coefficient of .70 was obtained. Data collected were analysed using frequencies and percentages. The results of the findings showed that the level of knowledge of physical health implications of STIs possessed by undergraduates of UNN was low (42.1%), their level of knowledge of social health implications of STIs was high (67.5%), and their level of knowledge of mental health implications of STIs was also high (65.3%). Based on the findings, conclusions were drawn and it was recommended that undergraduates’ curriculum should be diversified in order to accommodate topics on STIs, which could be inculcated in the general studies courses.